Short Communication: Genetic diversity of Ongole Grade Cattle of Rembang District, Central Java, Indonesia, based on blood protein polymorphism - SUTIYONO SUTIYONO; SUTOPO SUTOPO; Y. S. ONDHO; SETIATIN SETIATIN; D. SAMSUDEWA; A. SURYAWIJAYA; D. A. LESTARI; E. KURNIANTO (Society for Indonesian Biodiversity, 2018)
Sutiyono, Sutopo, Ondho YS, Setiatin ET, Samsudewa D, Suryawijaya A, Lestari DA, Kurnianto E. 2018. Genetic diversity of Ongole Grade Cattle of Rembang District, Central Java, Indonesia, based on blood protein polymorphism. Biodiversitas 19: 1429-1433. The objective of this study was to identify genetic diversity in Ongole Grade cattle of Rembang District, Central Java, Indonesia, based on blood-protein polymorphism. A total of 34 blood samples were collected from unrelated Ongole Grade cattle and the blood plasm was used to identify the blood proteins. Blood protein analysis was performed using Sodium Dodecyl Sulfate-Polyacrilamide Gel Electrophoresis (SDS-PAGE). Observed bands were used to perform allele interpretation of four loci, namely Albumin (Alb), Post-albumin (Po-Alb), Ceruloplasmin (Cp) and Amylase-1 (Am-1). Results showed the presence of polymorphism in all of the four blood-protein loci, average heterozigosity value (H) being 0.506 and almost all of the blood-protein loci studied showed deviation from Hardy-Weimberg Equilibrium (HWE). In conclusion, the study indicated that population of Ongole Grade cattle in Rembang, Indonesia has high genetic diversity.